The Obstetric Outcomes of Obese Primigravida with Spontaneous Onset of Labour at Term - Syed Mohd Ridzuan, Sharifah Nurul Inas; Ismail, Hamizah; Abd Aziz, Karimah Hanim; Abu Ishak , Nurkhairulnisa; Apparau, Aruku Naidu; Abu Bakar, Jumaida (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: Obesity has reached pandemic level with higher prevalence among women. Obese pregnant women have higher risk of comorbidities, maternal and fetal complications. This study aimed to determine the prevalence of vaginal delivery and pregnancy outcomes of obese primigravida presented with spontaneous labour at term. MATERIALS AND METHODS: This prospective cohort study was conducted in a tertiary hospital in Perak involving 250 obese primigravida (BMI ≥27.5kg/m2) and 250 non-obese primigravida. Data collected from August 2020 till January 2021 and analyzed using descriptive statistics, independent T-test and Mann-Whitney U test by SPSS version 23.0. RESULTS: Our study found that there were no significant differences in the proportion of vaginal delivery and caesarean delivery between obese and non-obese primigravida [72.0% vs. 78% (vaginal delivery) and 28% vs. 22% (caesarean delivery)] with spontaneous onset of labour at term. No difference in complications of labour such as PPH and OASIS (p=0.187), with high successful delivery without complications. Obese women presented with cervical dilatation of 4cm had longer delivery interval [5.82(2.97) vs. 4.75(2.71), p=0.013] but shorter delivery interval at 6cm [2.41(1.58) vs. 3.61(1.78), p=0.026] compared to non-obese. They also had higher caesarean rate indicated for abnormal labour progress [28(71.8) vs. 11(28.2), p=0.019] and higher comorbidities [149(72.3) vs. 57(27.7), p=<0.001]. There was no difference in the fetal outcome (p=0.311). CONCLUSION: After careful selection, obese women with spontaneous labour at term are safe for vaginal delivery as they have similar risk of labour augmentation, duration of active labour, caesarean delivery, PPH and OASIS despite higher comorbidities.